(untitled) (Global Journal of Science Frontier Research, 2017)
Land degradation in form of soil erosion and fertility loss are ruthless problems in developing countries including Ethiopian Highlands, which have serious implications for food security and livelihoods of local farmers in particular and the nation in general. Low land productivity due to land degradation in form of soil erosion is one of the leading challenges to improving the performance of the smallholder farming system sector in Ethiopia. In this context, the adoption of Sustainable Land Management practices/ technologies is quite crucial to increase agricultural productivity, ensure food security and improve the livelihoods of smallholder farmers. Farmers recommend various SLM practices/technologies for sustainable implementation, but adoption of such agricultural land management practices/ technologies is still very low. There is no clear understanding of the problems encountered by farmers in the adoption of recommended SLM practices/ technologies.